Potential diagnostic markers in nodular lesions of the thyroid gland: an immunohistochemical study - Rydlová, Marie; Ludvíková, Marie; Staňková, Ivana (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2008)
Aims: The diff erential diagnosis of thyroid nodules in routine practice can be problemmatic for both pathologistsand clinicians. Eff ective treatment requires a determination of the biological nature of the lesions. For this reason, ancilliarydiagnostic markers along with histological examination of the nodules may be useful. The objective of this studywas to evaluate the diagnostic usefulness of novel markers in the diagnosis of hyperplastic and neoplastic nodules.Methods: Forty eight thyroid lesions forming four diagnostic groups including adenomatous goiters (AS), follicularadenomas (FA), follicular (FC) and papillary carcinomas (PC) were examined using standard immunohistochemicalmethods. Monoclonal antibodies against galectin-3, matrix metalloproteinases (MMPs) -2 and -7 and endothelialmarkers CD31 and CD105 were used.Results: The cytoplasmatic expression of galectin-3 was positive in all cases of papillary carcinoma. Moreover,statistically signifi cant diff erences between fused groups of benign (AS and FA) and malignant lesions (FC and PC)were found Fischer’s exact test (p = 0.0001). No signifi cant diff erences in cytoplasmic expression of MMPs -2 and -7and in vascular density assessed by using of both endothelial markers between benign lesions and malignant tumorswere revealed.Conclusions: Galectin-3 appears to be a useful marker in the diagnosis of papillary carcinoma only. The matrixmetalloproteinases-2 and -7 are not helpful in distinguishing hyperplastic and neoplastic thyroid nodules. Endothelialmarkers do not appear to be suitable for thyroid diff erential diagnosis. A panel of antibodies in the diff erential diagnosisof thyroid nodular lesions would seem most suitable and further studies with larger sets of patients are awaited.
Keywords: nádory štítné žlázy; galektin 3; Statistics as Topic; diferenciální diagnóza; matrixové metaloproteinasy; statistika jako téma; Antibodies, Monoclonal; uzly štítné žlázy; Immunohistochemistry; lidé; Adenocarcinoma, Papillary; hyperplazie; Platelet Endothelial Cell Adhesion Molecule-1; imunohistochemie; Diagnosis, Differential; Thyroid Neoplasms; folikulární adenokarcinom; látky indukující angiogenezi; nádorové biomarkery; Galectin 3; antigeny CD31; receptory buněčného povrchu; Angiogenesis Inducing Agents; papilární adenokarcinom; Matrix Metalloproteinases; Biomarkers, Tumor; monoklonální protilátky; Receptors, Cell Surface; Thyroid Nodule; Hyperplasia; Adenocarcinoma, Follicular; Humans